Mercury intracellular partitioning and chelation in a salt marsh plant, Halimione portulacoides (L.) Aellen: Strategies underlying tolerance in environmental exposure - Válega, M. (2009)
http://www.sciencedirect.com/science/article/B6V74-4TWSWGV-2/2/fb5d4dd5d0727ea28abf40212d114131